Traumatic reticuloperitonitis in cattle and buffalo: Recent advances in understanding of etiopathogenesis, diagnosis and treatment - GUGJOO, MUDASIR BASHIR; DAR, SHAHID HUSSAIN; AHMAD, RAJA AIJAZ; HUSSAIN, HAKIM ATHAR; DAR, MEHRAJ DIN; PARRAH, JALAL-UD-DIN; DHAMA, KULDEEP (The Indian Journal of Animal Sciences, 2021)
Traumatic reticuloperitonitis (TRP) is one of the common ailments caused by ingestion of foreign bodies in adult large ruminants. It is mostly reported in stall fed animals or in animals of industrial areas and has huge economic importance. Its clinical signs are obvious but are obscured in the advanced chronic cases. Diagnosis of the condition is better done through the imaging techniques, although other ancillary tests like haemato-biochemical or physico-clinical examination aides in its confirmation. Treatment is undertaken either as conservative (medicine and magnets) or invasive (surgical) with the former options considered initially. Failure of the conservative treatment is followed by the surgical option and/ or the euthanasia or slaughter. Considering the importance of TRP and its limited know how in this part of the world, the current review details about the disease etio-pathogenesis, clinical signs, diagnosis and treatment. Finally, a conclusive statement over the disease is provided.